What Lay in the Abyss – A Faint Light in the Dark of Beyond the World’s End: Arts of Living at the Crossing (KULT_online, 2021)
Similar to previous publications of T.J. Demos, Beyond the World’s End: Arts of Living at the Crossing, is an urgent call to action that looks towards radical aesthetic practice for pragmatic solutions to the climate change crisis. This compilation of revised, previously published articles consists of close readings of contemporary artworks and social movements that act as case studies from which Demos develops and demonstrates his concept of ecology-as-intersectionality, an amalgamation of political ecology, critical race theory, and decoloniality.